Exchange Relationship between Companies and Competitors in Building Materials Retail Sector in Palu - Logianwy, Calvin Sovanno; Rembulan, Cicilia Larasati (Universitas Ciputra Surabaya, 2022)
Abstract Relation between firms and competitors are always related with rivalry in profit seeking, but the truth is, both firms and competitors can work together and fulfill each other’s requirement. This research aims to explore how exchange relation happens between firms and competitors in building materials sector retail. Participants in this study were 4 business owner. Data collection was conducted through interviews and documents. This study shows that focal firm coopeti-ed with competitors through informal interactions by several situation that causes them to cooperate and compete. When both sides compete, this research found several things that are being competed by both sides, and when they cooperate, this research found several exchanged resources along with the benefit for both parties. Additional findings in this research are the appearance of coexistence relation between focal firms and competitors which is not the focus of this research, and how there is good and bad competitors in business. Keyword : Coopetition, Resource Exchange, Building Materials Sector Retail, Competitor